BigBasket (a) - Roy, Debjit; Anand, Abhishek (London : Indian Institute of Management, Ahmedabad, 2020)
The BigBasket case examines the governing factors that determine the business model in the online grocery market. Established in 2011, BigBasket started as a hyperlocal model, and quickly transformed its business to follow the inventory-based model. Accordingly, it scaled its business operation in the limited cities it was operating in. However, the business strategy was quite contrary to the flavor of the season, the hyperlocal model. BigBasket took the conventional retail route of managing its own inventory at a time when on-demand service-based hyperlocals were in vogue. Investors were pouring money into a number of startups in the e-grocery space.Although BigBasket was an early starter, many contemporary competitors had moved ahead in a number of cities. The funding trends too reflected the market belief in the hyper-local model. BigBasket's rationale to follow the inventory-based model came from the extensive experience of the founding members who were pioneers in the field. They had a good understanding of how the Indian grocery market operated and they understood the ethos of the grocery business.With the future expansion plan and fundraising series in hand, BigBasket could redraw the strategy. Should BigBasket reconsider its decision to follow the inventory-based business? Should it transform itself into a completely hyperlocal business or should it operate different models in different markets? Would the hyperlocal model help BigBasket to scale its business rapidly? If scalable, is a hyperlocal model sustainable in the Indian online grocery market?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic commerce; Internet marketing; Inventory control -- Technological innovations; Grocery trade -- Management